2008
DOI: 10.1007/s11738-008-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ribonuclease and protease activities in germinating rice seeds exposed to nickel

Abstract: When the seeds of two rice cvs. Malviya-36 and Pant-12 were germinated up to 120 h in the presence of 200 and 400 lM NiSO 4 , a significant reduction in the germination of seeds occurred. Seeds germinating in the presence of 400 lM NiSO 4 showed about 12-20% decline in germination percent, about 20-53% decline in lengths and about 8-34% decline in fresh weights of roots and shoots at 120 h of germination. Ni 2+ exposure of germinating seeds resulted in apparent increased levels of RNA, soluble proteins, and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…However, high levels of Ni in the growth medium has led to a marked inhibition of germination and has delayed the time necessary to achieve 50% germination (Espen et al 1997;Leon et al 2005). Maheshwari and Dubey (2008) reported a significant reduction in the germination of rice seeds, when high concentrations of Ni were present. These authors showed that exposure of seedlings to Ni for 120 h reduced germination by 12-20%, reduced plumule and radicle lengths by 20-53%, and reduced fresh weight by 8-34%.…”
Section: Germination Percentage and Ratementioning
confidence: 99%
“…However, high levels of Ni in the growth medium has led to a marked inhibition of germination and has delayed the time necessary to achieve 50% germination (Espen et al 1997;Leon et al 2005). Maheshwari and Dubey (2008) reported a significant reduction in the germination of rice seeds, when high concentrations of Ni were present. These authors showed that exposure of seedlings to Ni for 120 h reduced germination by 12-20%, reduced plumule and radicle lengths by 20-53%, and reduced fresh weight by 8-34%.…”
Section: Germination Percentage and Ratementioning
confidence: 99%
“…These proteins were involved as oxidative scavengers of the reactive oxygen species, and interacted with the aldehyde products that usually release from lipid peroxidation (Sandalio et al, 2001). The role of newly expressed proteins in binding Cd ion forming polychelatins and metallothioneins, then placed them in the vacuole was also suggested (Maheshwari and Dubey, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…RNases and proteases activity is essential for breakdown of protein, their recycling and amino acids mobilization towards the growing embryo in seeds (Palma et al, 2002;Yamauchi, 2003). Disturbed activity of both these enzymes under metal stress resulted in altered protein and amino acids levels in germinating seeds (Maheshwari and Dubey, 2008). The two chelators-natural (Oxalic acid) and synthetic (EDTA) relieve the stress on α-amylase and protease activity by subdue the availability of Cd ions in growth medium, consequently the activity of both the enzymes was not severely affected (Zeid, 2001).…”
Section: Discussionmentioning
confidence: 99%